(untitled) - Hoffmann, Frank W. (Lanham, Md., 2007)
The book represents an ongoing effort to fill the void in the library literature relating to collection development policies for school libraries and to assist both library school students and professionals in the field with the compilation, revision, and implementation of policies
Keywords: Collection development (Libraries),Collection development (Libraries),Phát triển bộ sưu tập (thư viện),Phát triển bộ sưu tập (thư viện); United States,United States,Hoa Kỳ,Hoa Kỳ